THE EFFECT OF LEARNING INTEREST AND LEARNING RESOURCE UTILIZATION ON ECONOMICS ACADEMIC ACHIEVEMENT OF GRADE XI STUDENTS AT PEMATANGSIANTAR TELADAN PRIVATE HIGH SCHOOL - Delima Br Simbolon; Sotarduga Sihombing; Anggun Tiur Ida Sinaga; Herlina Hotmadinar Sianipar (RADJA PUBLIKA, 2025)
This study aims to determine the effect of learning interest and the utilization of learning resources on students' academic achievement in economics among Grade XI students at SMA Swasta Teladan Pematangsiantar. The background of this research stems from the low scores in the odd semester final exam for economics, indicating a lack of interest in learning and suboptimal use of available learning resources. This study employs a quantitative approach with a descriptive research design. The population consists of all Grade XI students at SMA Swasta Teladan Pematangsiantar for the 2024/2025 academic year, totaling 243 students. A proportional sampling technique was used to select 90 students as the sample. Data were collected using questionnaires for the variables of learning interest and the utilization of learning resources, as well as documentation of midterm exam (UTS) scores in economics as an indicator of academic achievement. Data analysis techniques include simple linear regression, multiple linear regression, t-test, F-test, and the coefficient of determination. The prerequisite test used chi-square normality tests, and the results showed that the data were normally distributed. The analysis results showed a positive and significant effect of learning interest on academic achievement (tcount=7.946 > ttable=1.987) and a positive and significant effect of the utilization of learning resources on academic achievement (tcount=6.124 > ttable=1.987). The F-test results also showed that both variables simultaneously had a significant effect on students' academic achievement (Fcount=24.627 > Ftable=3.10). The coefficient of determination (R²) was 0.361, indicating that 36.1% of the variation in students' academic achievement was influenced by learning interest and the utilization of learning resources, while the remaining 63.9% was influenced by other factors not examined in this study.